Interleukin 1α-Deficient Mice Have an Altered Gut Microbiota Leading to Protection from Dextran Sodium Sulfate-Induced Colitis - Nunberg, Moran (mSystems, 2018)
Inflammatory bowel diseases (IBD) are a group of chronic inflammatory disorders of the intestine, with as-yet-unclear etiologies, affecting over a million people in the United States alone. With the emergence of microbiome research, numerous studies have shown a connection between shifts in the gut microbiota composition (dysbiosis) and patterns of IBD development. In a previous study, we showed that interleukin 1α (IL-1α) deficiency in IL-1α knockout (KO) mice results in moderate dextran sodium sulfate (DSS)-induced colitis compared to that of wild-type (WT) mice, characterized by reduced inflammation and complete healing, as shown by parameters of weight loss, disease activity index (DAI) score, histology, and cytokine expression. In this study, we tested whether the protective effects of IL-1α deficiency on DSS-induced colitis correlate with changes in the gut microbiota and whether manipulation of the microbiota by cohousing can alter patterns of colon inflammation. We analyzed the gut microbiota composition in both control (WT) and IL-1α KO mice under steady-state homeostasis, during acute DSS-induced colitis, and after recovery using 16S rRNA next-generation sequencing. Additionally, we performed cohousing of both mouse groups and tested the effects on the microbiota and clinical outcomes. We demonstrate that host-derived IL-1α has a clear influence on gut microbiota composition, as well as on severity of DSS-induced acute colon inflammation. Cohousing both successfully changed the gut microbiota composition and increased the disease severity of IL-1α-deficient mice to levels similar to those of WT mice. This study shows a strong and novel correlation between IL-1α expression, microbiota composition, and clinical outcomes of DSS-induced colitis. IMPORTANCE Here, we show a connection between IL-1α expression, microbiota composition, and clinical outcomes of DSS-induced colitis. Specifically, we show that the mild colitis symptoms seen in IL-1α-deficient mice following administration of DSS are correlated with the unique gut microbiota compositions of the mice. However, when these mice are exposed to WT microbiota by cohousing, their gut microbiota composition returns to resemble that of WT mice, and their disease severity increases significantly. As inflammatory bowel diseases are such common diseases, with limited effective treatments to date, there is a great need to better understand the interactions between microbiota composition, the immune system, and colitis. This study shows correlation between microbiota composition and DSS resistance; it may potentially lead to the development of improved probiotics for IBD treatment.